The EU, ASEAN and interregionalism: regionalism support and norm diffusion between the EU and ASEAN - Allison, Laura; SpringerLink (Online service) (London : Palgrave Macmillan UK, 2015)
Using a framework of norm diffusion to determine the EU's international actorness in the context of its relations with ASEAN, this book provides a timely and in-depth analysis of EU-ASEAN relations. By investigating three aspects of regionalism support by the EU it presents a comprehensive account of norm diffusion between the EU and ASEAN.
Keywords: Political science; Asia -- Politics and government; European Union; International relations; Diplomacy; Globalization